MUESLI - a Material UnivErSal LIbrary. (March 2017) - Portillo, David; del Pozo, Daniel; Rodríguez-Galán, Daniel; Segurado, Javier; Romero, Ignacio
Highlights: It provides functions for the mechanical and thermal response of the most commonly employed models in small and large strain solid mechanics, thermal analysis, fluid mechanics. The library is object oriented, with a structure that makes it easy to extend it to new materials. The source code is freely available under GNU 3.0 license. The library can be included in research codes, and interfaces are provided for two commercial codes. In this way, the same material models developed in MUESLI can be employed within commercial codes, without any modification. Automatic tests are included that verify the consistency of the implementation, helping furthermore to debug new implementations. Abstract: This article describesMUESLI, an open source library with constitutive models of continuum materials for solid, fluid, and thermal problems available athttp://www.materials.imdea.org/Muesli . The library is object oriented, and includes the most commonly employed material models in Computational Mechanics. It is designed for easy extension, and includes classes for tensor manipulation and automatic testing. The library can be linked to existing codes, including commercial ones, for some of which specific interfaces are provided.